Effectiveness Of Providing Breast Care Education On Mother Skills In Breastfeeding Mothers - Fanesha Ayuni Filiasari; Firdawsyi Nuzula; Siswoto Hadi Prayitno (Pusat Penelitian dan Pengabdian Masyarakat STIKES Banyuwangi, 2026)
Breast care is essential for every pregnant mother to ensure smooth breast milk production. With sufficient breast milk production, the baby's nutritional adequacy will be met. Breast care is an important thing to pay attention to in preparation for breastfeeding, because the breast is an important organ that produces breast milk. This research aims to evaluate and determine the extent to which providing breast care education can improve mothers' skills. The quantitative research method uses a pre-experimental method, using a one-group pretest-posttest approach. a population of 500 respondents with a purposive sampling technique was 83 respondents with the criteria of breastfeeding mothers 0-6 months (exclusive breastfeeding) in the work area of the Kalibaru Kulon Community Health Center. Data was collected in the form of breast care SOPs and checklist sheets according to the SOP. The statistical test results of the Wilcoxon test are known as Asymp.sig. (2-tailed) has a value of .000 < 0.05, it is concluded that there is an influence of breast care education on maternal skills in breastfeeding mothers in the working area of the Kalibaru Kulon Community Health Center. Providing breast care education regarding maternal skills to breastfeeding mothers is very important to facilitate the release of breast milk, and helps increase blood flow and keep the milk ducts from becoming blocked, helping to keep the breasts and nipples healthy and clean